1989
DOI: 10.1002/mrd.1120240305
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold distribution of actin during sperimiogenesis in the normal rabbit and after experimental cryptorchidism

Abstract: Immunogold procedures for actin detection were used in combination with experimental cryptorchidism in the rabbit as a model to shed more light on the function of subacrosomal actin during spermiogenesis. In the normal testis, actin was localized in the perinuclear substance (PNS) from round spermatid onward but it was not detected in late spermatids. Actin labeling in each type of spermatid was essentially unmodified after 24 hr of cryptorchidism. However, among relevant immediate and delayed effects, discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This feature is observed in several mammalian spermatozoa types such as ground squirrel , rat (Russell et al, 1986;Fouquet et al, 1989a), boar (Camatini et al, 1986), hamster, monkey, human (Fouquet et al, 1989a(Fouquet et al, , 1990, and rabbit (Camatini et al, 1987;Fouquet et al, 1989b). In late spermatids there are both depolymerization of subacrosomal F-actin and a loss of actin immunolabeling, suggesting a dispersion of G-actin or G-actin relocation to other sperm regions, or protein masking (Fouquet et al, 1990).…”
Section: Actinmentioning
confidence: 83%
“…This feature is observed in several mammalian spermatozoa types such as ground squirrel , rat (Russell et al, 1986;Fouquet et al, 1989a), boar (Camatini et al, 1986), hamster, monkey, human (Fouquet et al, 1989a(Fouquet et al, , 1990, and rabbit (Camatini et al, 1987;Fouquet et al, 1989b). In late spermatids there are both depolymerization of subacrosomal F-actin and a loss of actin immunolabeling, suggesting a dispersion of G-actin or G-actin relocation to other sperm regions, or protein masking (Fouquet et al, 1990).…”
Section: Actinmentioning
confidence: 83%
“…The role of F-actin and of its interaction with other perinuclear theca proteins is not known. Possible roles are anchorage of the acrosome [17,22,27,29] or shaping of the head by capping the nuclear membrane [26,30].…”
Section: Introductionmentioning
confidence: 99%
“…The subacrosomal layer of mammalian spermatids is also filled with actin, one of the ubiquitous cytoskeletal proteins, in its filamentous form (F-actin) during the greater part of spermiogenesis [20][21][22][23][24][25][26][27][28]. In late spermatids and spermatozoa of many species, most or all of the F-actin is depolymerized to G-actin and seems to be redistributed in a species-specific pattern [2,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years normal spermatid morphogenesis was compared with pathological models: the experimentally cryptorchid rabbit [55] and mutant and transgenic mice [56][57][58]. These investigations have led to the following conclusions: 1) from round spermatid onwards, the polarity of the A variety of methods have demonstrated that the sperm plasma membrane is a mosaic of domains [5].…”
Section: Sperm Head Morphogenesismentioning
confidence: 99%